Phosphorus and Calcium Utilization and Requirements in Farm Animals - Vitti, Dorinha M.S.S (CABI, 2014)
Ever since animal agriculture began there has been a drive to improve the productivity of our livestock for economic and survival reasons. For that reason research into animal production has been concerned largely with this objective. The limits on production in early days of agriculture were determined by the natural regenerative processes of the soil and the cycling of crop and animal wastes in a closed, ecologically sustainable system (Conway and Pretty, 1991). Since the Second World War, a tremendous improvement in agricultural production has been observed. This is mainly due to national and international policies that were favourable to farming such as the European Common Agricultural Policy and major technological advances in inputs and techniques available to farmers. Intensification of animal production led to a serious imbalance between inputs of nutrients in purchased fertilizers, concentrates and forages, and the respective outputs in milk and meat and nutrient accumulation in the environment. Several surveys (e.g. Sansinena et al., 1999; Satter and Wu, 1999; Sink et al., 2000; Kebreab et al., 2008) have revealed that dairy producers in the United States and Canada routinely include 0.45 to 0.50% dietary P in feed. This is in excess of recommendations by NRC (2001) and in excess of the needs of lactating cows (Wu et al., 2001; Valk et al., 2002). Castillo et al. (2009) reported that 62.5% of California dairies fed P in the amounts 120–200% of NRC requirements to their herd. Similarly, 21 out of 40 commercial dairy farms tested in Merced County, California, had 120–200% of NRC requirements of Ca. None of the farms fed P below requirement and all farms fed iron and manganese over 200% of NRC requirements.